UTOPIA KHILÄ€FAH ISLÄ€MIYYAH: Studi Tafsir Politik Mohammed Arkoun - Muqtada, Muhammad Rikza (Jurnal THEOLOGIA, 2017)
Abstract: This paper aims to study Muhammed Arkounâ€™s political interpretation thought about the ideal state. He shows that each political contestation often uses religion as a legitimation of political interest. Many of discourses in Qurâ€™an, such as old narratives of Qurâ€™an (amtsal al-Qurâ€™an), is often presented to modify the existing political conditions. Moreover, some of the terms of Quranic discourse, like as â€˜Muslimâ€™ or â€˜Kafirâ€™ (infidel), is always in a binary position to create sharp differences between the militant and the opposition. The Qur'anic discourses, intentionally or not, since the time of revealing of the Qurâ€™an has been dragged into the political territory as well the theological territory, so it is able to change the profane history into the sacred story with the great power of sacralization. Although the Qurâ€™an is within the dialectic area, some of Islamist always reduces the meaning of Qurâ€™an to support their agenda in realizing the Islamic State (Khilafah Islamiyah). For Arkoun, that desire is a utopian politics idea and nothing more than an interpretation of religious texts. There is no agreement among the people about the ideal state concept. Therefore, Arkoun offers the concept of ideal state is if religious authorities and political authorities apply their function professionally yet integrated.Abstrak: Tulisan ini menggagas pemikiran tafsir politik Muhammed Arkoun tentang negara ideal. M. Arkoun menggambarkan bahwa dalam setiap kontestasi politik sering menyeret agama sebagai legitimasi pemangku kepentingan. Wacana-wacana dalam al-Qurâ€™an seperti teladan-teladan kuno (amthÄl al-Qurâ€™an) sering dihadirkan untuk memodifikasi kondisi politik yang ada. Selain itu, beberapa istilah dalam wacana al-Qurâ€™an, seperti â€˜Muslimâ€™ dan â€˜kafirâ€™, diposisikan biner untuk menciptakan perbedaan tajam antara kelompok militan dan oposan. Wacana-wacana qurâ€™ani tersebut, dengan sengaja atau tidak, sejak masa turunnya ayat telah diseret masuk ke dalam wilayah politik sekaligus wilayah teologis, sehingga mampu mengubah sejarah yang profan menjadi kisah sakral dengan kekuasaan sakralisasi yang besar. Meskipun al-Qurâ€™an berada dalam ruang dialektis yang bebas, oleh sebagian kelompok Islamis pemaknaan al-Qurâ€™an direduksi dan dibawa untuk mendukung agenda mewujudkan Islamic State (negara Islam). Bagi Arkoun, keinginan tersebut merupakan gagasan politik yang utopis dan tak lebih dari sebuah interpretasi atas teks agama. Tidak ada kesepakatan di kalangan umat mengenai konsep negara ideal. Karena itu, Arkoun menawarkan konsep negara ideal adalah jika otoritas keagamaan dan otoritas politik berlaku sesuai dengan fungsinya namun tetap terintegrasi.